Impacts of different wind and solar power penetrations on cascade hydroplants operation. (January 2022) - Jin, Xiaoyu; Liu, Benxi; Liao, Shengli; Cheng, Chuntian; Li, Gang; Liu, Lingjun
Abstract: The changing energy mix under the integration of wind and solar power widens the load peak-valley difference of the power grid and poses great challenges in power grid operation, especially for peak shaving. Hydropower has a crucial role to play in enabling the integration of more variable renewables. To explore a reasonable approach for the changing roles of hydropower and the development of wind and solar power in response to energy transition, a long-term typical daily aggregate model is developed for hydro-wind-solar power with peak shaving operation. Scenarios of integrated wind and solar power proportions under increasing penetrations are simulated by incrementally increasing the installed wind and solar power capacity. The model is converted to a mixed integer linear programming formulation. Groups of numerical experiments divided by influencing factors are used to analyze the complementary influence and optimization mechanisms. The results demonstrate that (1) the proposed model decouples hydro-wind-solar sources at temporal scales and conducts peak shaving effectively. (2) Different scales of wind and solar power have notable impacts on both long-term and short-term hydropower operation. (3) Developing wind and solar power in reasonable proportions could effectively utilize the complementarity and reduce hydropower output fluctuations on different time scales. Highlights: A model optimizing the long-term coupled short-term hydro-wind-solar peak shaving operation for a regional power grid was proposed. Scenarios with different integrated wind and solar power proportions were modeled under increasing penetrations. The impacts of the hydro-wind-solar integration system was analyzed in terms of hydrological regimes and temporal scales. The balanced development of wind and solar power was proven to be conducive to hydropower operational control.